Perbaikan Kualitas untuk Mengurangi Tingkat Kecacatan pada Produk Kain Grey dengan Menggunakan Metode Teoriya Resheniya Izobreatatelskikh Zadatch (TRIZ) di PT. Dewy Textile Factory - Friedo Irwan Oktavian; Aviasti (UNISBA Press, 2023)
Abstract. PT Dewy Textile Factory is a textile company that manufactures greige fabric products. Greige fabric is unfinished knitted fabric. The total production of greige fabric in the period January - October 2021 is 17,694 rolls. The average rate of defective products produced is 5.36% of total production which exceeds the tolerance limit set by the company at 5%. To overcome this problem, it is necessary to conduct research on quality improvement to identify the causes of defects and provide recommendations for improvements to reduce the rate of defects in greige fabric products. The basic causes of the problems are identified using the FTA method while the proposed improvements are made using the TRIZ method. According to the results of data processing, it was found that the most basic causes that resulted in defects in greige fabric products were mechanics not understanding production directions, monitoring of needle spare parts not carried out regularly, air circulation was not smooth, lack of supervision of the production process by operators, high temperatures, inadequate quality control of raw materials carried out regularly, the operator is not focused, the operator is not skilled, and the environment is less clean. Proposed improvements to reduce the defect rate of greige fabric products are implementing training and making capability assessment documents for mechanics, making needle monitoring reports, adding exhaust fan facilities, providing additional breaks, making checksheets for checking raw thread materials, loading visual controls, implementing training and create capability assessment documents for mechanics, schedule regular pickets, and add vacuum cleaner facilities. Abstrak. PT Dewy Textile Factory adalah perusahaan tekstil pembuat produk kain grey. Kain grey merupakan kain hasil rajutan yang belum melalui tahap finishing. Total produksi kain grey pada periode Januari - Oktober 2021 adalah sebanyak 17694 rol. Rata – rata tingkat produk cacat yang dihasilkan sebesar 5,36%, hal ini melebihi batas toleransi yang ditetapkan oleh perusahaan sebesesar 5% dari total produksi. Untuk mengatasi masalah tersebut maka perlu dilakukan penelitian mengenai perbaikan kualitas untuk mengidentifikasi penyebab masalah kecacatan dan memberikan usulan perbaikan untuk mengurangi tingkat kecacatan produk kain grey. Penyebab dasar permasalahan diidentifikasikan dengan menggunakan metode FTA sedangkan usulan perbaikan dilakukan dengan menggunakan metode TRIZ. Berdasarkan hasil pengolahan data didapatkan penyebab dasar yang mengakibatkan kecacatan kain grey yaitu mekanik tidak memahami arahan produksi, pengawasan spare part jarum tidak dilakukan secara berkala, sirkulasi udara tidak lancar, kurangnya pengawasan proses produki oleh operator, suhu tinggi, kontrol kualitas bahan baku tidak dilakukan secara berkala, operator tidak fokus, operator tidak terampil, dan lingkungan kurang bersih. Usulan perbaikan untuk mengurangi tingkat kecacatan kain grey adalah memberlakukan pelatihan dan membuat dokumen penilaian kemampuan bagi mekanik, membuat laporan monitoring jarum, menambahkan fasilitas exhaust fan, memberikan istirahat tambahan, membuat checksheet pemeriksaan bahan baku benang, memuat visual control, memberlakukan pelatihan dan membuat dokumen penilaian kemampuan bagi mekanik, membuat jadwal piket secara berkala, dan menambahkan fasilitas vacum cleaner.